PENGARUH PENERAPAN MANAJEMEN RISIKO TERHADAP NILAI PERUSAHAAN BANK KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setyoko, Priyo Dani; Simanjutak, Jontro (SCIENTIA JOURNAL, 2021)
ABSTRACT Banking is a milestone for the economy of a country, including Indonesia because banking has a very important role. Therefore, it is necessary to implement risk management to offset the increasing risks faced by banks and to cover fixed costs or fixed expenses of the company. This study is to determine the effect of the application of risk management on the firm value of conventional banks listed on the IDX. The implementation of risk management is measured by three models. The first method uses the ratio of net interest margin (NETIM), non-interest margin (NONIM), provision for impairment loss (PROV) and uses the capital adequacy ratio (CAR). Then the second method uses the average value (AVG) of these ratios and the third method uses the principal Component analysis (PCA) value of these ratios. Then in analyzing the impact of the application of risk management on firm value using panel data regression analysis. The regression model used is the fixed effect model. The yield of the study show that each method of implementing risk management has different results. In the first method, NONIM and CAR ratios have a positive effect but there is no significant effect, NETIM and PROV have a negative effect but there is no significant impact on firm value. In the second method, the average value has a positive effect but there is no significant impact on firm value. In the third method, the PCA value has no significant impact on firm value.